Brentuximab Vedotin in Transplant‐Naïve Relapsed/Refractory Hodgkin Lymphoma: Experience in 30 Patients. (23rd October 2015) - Zinzani, Pier Luigi; Pellegrini, Cinzia; Cantonetti, Maria; Re, Alessandro; Pinto, Antonello; Pavone, Vincenzo; Rigacci, Luigi; Celli, Melania; Broccoli, Alessandro; Argnani, Lisa; Pulsoni, Alessandro
Abstract : Background: Hodgkin lymphoma (HL) is characterized by the presence of CD30‐positive Hodgkin Reed‐Sternberg cells. Approximately 30%–40% of patients with advanced disease are refractory to frontline therapy or will relapse after first‐line treatment. The standard management of these patients is salvage chemotherapy followed by high‐dose chemotherapy and autologous stem cell transplant (ASCT). The best prognostic factor is the status of disease before ASCT; in particular, the normalization of positron emission tomography (PET) scan. Brentuximab vedotin (BV) has shown a high overall response rate in refractory/relapsed HL after ASCT, whereas few data are available regarding its role before ASCT. Patients and Methods: A multicenter, retrospective, observational study was conducted. The primary endpoint of the study was the effectiveness of BV as single agent in patients with relapsed/refractory, ASCT‐naïve HL, determined by the conversion of PET status from positive to negative; secondary endpoints were safety, capacity to proceed to ASCT, survival, and progression‐free status. Results: Thirty patients with relapsed/refractory HL‐ and PET‐positive disease after conventional chemotherapy salvage treatments were treated with a median of 4 cycles of BV. Normalization of PET findings (Deauville score ≤2) occurred in 9 of 30 patients (30%). Those nine patients proceeded to ASCT. Conclusion: These data suggest that BV can normalize PET status in a subset of HL patients refractory to conventional chemotherapy salvage treatments, such as ifosfamide‐containing regimens, cytarabine‐ and platinum‐containing regimens, prior to ASCT. Implications for Practice: Administration of brentuximab vedotin has resulted in a high overall response rate in refractory/relapsed Hodgkin lymphoma after autologous stem cell transplant, whereas few data are available regarding its role before transplant. The data suggest that brentuximab vedotin can normalize positron emission tomography results in a subset of patients refractory to conventional salvage treatments prior to transplant. Experience indicates that patients previously regarded as not ideal candidates for transplantation may be able to undergo further cytoreductive therapy using brentuximab vedotin. Abstract : This study evaluated the effectiveness of brentuximab vedotin (BV) in 30 autologous stem cell transplantation (ASCT)‐naïve patients with relapsed/refractory Hodgkin lymphoma and positron emission tomography‐positive (PET) disease after conventional chemotherapy salvage treatments. The primary endpoint was the conversion of PET‐positive to PET‐negative status after four cycles of BV. PET normalization occurred in nine patients; these patients subsequently received ASCT.